2019
DOI: 10.1111/ajag.12691
|View full text |Cite
|
Sign up to set email alerts
|

Putting the consumer in the driver's seat: A visual journey through the Australian health‐care system as experienced by people living with dementia and their carers

Abstract: Objective: To better understand the individual journeys of people living with dementia and their carers through the Australian health-care system. Methods: Stories were collected from 25 participants, through five face-to-face workshops, across Australia. This produced 18 visual storyboards and a range of opportunities for improvement, which were then synthesised into an aggregated "idealjourney" model. Results: Several issues were identified: long lead times to diagnosis; diverse experiences of treatment and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 5 publications
0
9
0
3
Order By: Relevance
“…Although professional organizations have developed materials related to dementia resources, participants from four included studies identified several barriers related to accessing dementia information and services 6,10,39,42 . Prior research has suggested that persons with dementia and their caregivers often found it difficult to navigate the healthcare system and obtain relevant information about dementia 52,53 . Therefore, future interventions are needed to incorporate information about local resources that can more easily be accessed by older adults and their families.…”
Section: Discussionmentioning
confidence: 99%
“…Although professional organizations have developed materials related to dementia resources, participants from four included studies identified several barriers related to accessing dementia information and services 6,10,39,42 . Prior research has suggested that persons with dementia and their caregivers often found it difficult to navigate the healthcare system and obtain relevant information about dementia 52,53 . Therefore, future interventions are needed to incorporate information about local resources that can more easily be accessed by older adults and their families.…”
Section: Discussionmentioning
confidence: 99%
“…This has driven research which explores the ‘older persons' consumer experience’ 7–10 . For example, research has focused on the development of ‘older persons' care consumer experience’ surveys, 7,10 consumer experiences of home care packages, 6 older persons' consumer needs 11,12 and dementia care from the consumers' perspective 13 …”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] For example, research has focused on the development of 'older persons' care consumer experience' surveys, 7,10 consumer experiences of home care packages, 6 older persons' consumer needs 11,12 and dementia care from the consumers' perspective. 13 Despite this move to a more consumer-centric model, there are still many misunderstandings around older people, their needs and how to communicate effectively with them. 14 While previous studies have provided insight into elements of the lived experience for older people, very little research has explored the components of satisfaction for this group.…”
Section: Introductionmentioning
confidence: 99%
“…According to an influential report by the Alzheimer's Disease International Organization [14], «national dementia strategies should promote early diagnosis and intervention». It is worth noting that families of PwD need a timely diagnosis, in order patients and their caregivers be able to understand the care plan and comply with the medical guidelines as the disease progresses [15,16]. Also, the way in which the diagnosis is announced, as well as the support provided after the diagnosis, can impact on caregivers' adjustment during care [14,17].…”
mentioning
confidence: 99%